Analysis and Design of Plug Shape of an Aerospike Nozzle - Omar Abada; Abderahim Abada; Hakim Kbab; Ahmed Abdallah Elhirsti (AVIA, 2022)
The present work investigates the influence of gas at high temperature on the design and analysis of two-dimensional plug nozzle. The thermochemical and combustion studies of liquid launchers propellants make it possible to choose the gases to be studied. For example, four cases of bi-propellants engines have been studied. The combinations studied are: H2/O2, RP1/O2, CH4/O2 et MMH/N2O4. The selected gas are: CO2, H2O H2, N2 and CO. Once the profile is generated, an analysis of the thermodynamic-parameters evolution (such as: length, Mach number, mass, thrust coefficient) and aerodynamic performances is conducted. Some results were presented and compared with previous research using air. The comparison shows that the presence of H2O and CO2 gases considerably increases the performance of nozzles. The percentage of gases in the combustion has an influence on these increases. In order to minimize the weight of this nozzle, the truncation of Plug nozzle in order to increase their performances is studied in this research.